Cyclic pressure variations in a small diesel engine fueled with biodiesel and antioxidant blends - Mohd Hafiz, Ali; Abdul Adam, Abdullah; Mohd Hafizil, Mat Yasin; Mohd Kamal, Kamaruzzaman (Universiti Malaysia Pahang, 2020)
Biodiesel fuel is considered as one of the most competence sustainable replacement for fossil fuel due to their superior combustion characteristics and possesses higher oxygen content. Thus, many researchers recently investigated to improve biodiesel capability by adding additives whether by blending with dual-fuel or tri-fuel. However, the combustion characteristics for biodiesel and biodiesel-additives blends are not thoroughly examined and need additional research works to study how the biodiesel behaviour and characterise. Thus, this research main objective is to study a single-cylinder diesel engine cyclic cylinder pressure variations running with biodiesel with antioxidant (B2HA1.0 and B2HT 1.0) blends with palm oil methyl ester (POME). While The baseline fuels used for this study were biodiesel (B20) and pure diesel (B0). The entire test fuels were examined at a constant engine speed 1800 rpm with 100% engine load condition. The engine combustion characteristics were studied by utilising the indicated mean effective pressure (IMEP) and cyclic variations of combustion pressure at 200 consecutive cycles. Combustion characteristics of engine diesel have been studied by using statistical analysis. The results revealed that the engine running with biodiesel-antioxidants have higher cyclic variations of combustion from B20 and B0, which B2HA1.0 possessed the highest cyclic variations. It can be summarised from the study that biodiesel-antioxidants fuels produce a substantial influence on the engine cyclical variation, which linked to the characteristics of the engine combustion.